2002
DOI: 10.1016/s0022-5347(05)64550-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Weekly Intravenous Gemcitabine Administration With Interferon and Interleukin-2 Immunotherapy for Metastatic Renal Cell Cancer

Abstract: Despite the small sample size, this study demonstrates that gemcitabine combined with standard doses of IFN-alpha and low doses of IL-2 is effective treatment for metastatic renal cell carcinoma. This biotherapy was well tolerated and resulted in an optimum objective response and relatively long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…14,18 At least two other gemcitabine-based Phase II studies have reported higher response rates (31% in a single-agent feasibility study 15 and 28% for the combination of gemcitabine, IL-2, and interferon-␣. 17 ) than the one noted in the current study. However, the small number of patients enrolled in those studies (16 and 18, respectively) may be indicative of a relevant bias.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…14,18 At least two other gemcitabine-based Phase II studies have reported higher response rates (31% in a single-agent feasibility study 15 and 28% for the combination of gemcitabine, IL-2, and interferon-␣. 17 ) than the one noted in the current study. However, the small number of patients enrolled in those studies (16 and 18, respectively) may be indicative of a relevant bias.…”
Section: Discussioncontrasting
confidence: 54%
“…10 More recently, it has been shown that gemcitabine-containing combinations also exert some antitumor activity in patients with immunotherapy-resistant advanced RCC. [11][12][13][14][15][16][17][18][19][20] Herein, we report the results of a single-institution Phase II study in which we evaluated the antitumor activity and toxicity of a combination of gemcitabine with the platinum derivative oxaliplatin (L-OHP).…”
mentioning
confidence: 99%